Gratitude as Social Capital of Happiness: Working Wives’ Perceptions of Husbands’ Social Support in the Islamic Marriage Context - Sururin, Sururin; Nihayah, Zahrotun; Choirunnisa, Choirunnisa; Hidayat, Dinnisa Haura Zhafira; Alim, Syahirul; Ramadhan, Syahrul (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
In Indonesia, rising dual-income families increase potential marital conflicts, yet few studies explore how Islamic psychological perspectives (happiness and gratitude) explain marital resilience. This highlights the urgency of examining wives’ perceptions of husbands’ support and its impact on gratitude. This study aims to examine the influence of wives’ happiness and husbands’ social support on gratitude among working Muslim wives. Employing a cross-sectional study with a quantitative approach, this study specifically involved married, moslem, working women with children as the study's population. Sampling was done by non-probability sampling technique where the number of samples in the study was 225 married Muslim working women with children. The instrument in this study uses the adoption of the Gratitude Questionnaire (GQ-6, α = 0.82), Husband’s Social Support Scale (32 items, α = 0.91), and Islamic Happiness Scale (18 items, α = 0.88) and analysis with multiple linear regression (SPSS 22). All instruments were validated through expert judgment and pilot testing. Regression analysis confirmed that both happiness (β = 0.128, p = 0.004) and husband’s social support (β = 0.743, p = 0.000) significantly predicted gratitude (R² = 0.648). These findings support the study hypotheses and demonstrate the role of emotional and relational factors as social capital in sustaining marital harmony within an Islamic framework. Good interpersonal relations, as shown through the attitude of gratitude of husband, and wife, are social capital in achieving happiness.